Apoptotic effect of hot water extract of Sanguisorba officinalis L. in human oral cancer cells - SHIN, JI-AE (D.A. Spandidos, 2012)
Sanguisorba officinalis L. has been used in traditional Asian medicine to treat diseases including diarrhea, chronic intestinal infections, duodenal ulcers and bleeding. This study examined the antiproliferative effects and apoptotic activity of hot water extract of S. officinalis L. (HESO) on HSC4 and HN22 human oral cancer cells. The effects of HESO were evaluated by the 3-(4,5-dimethylthiazol-20yl)-(3-carboxymethoxyphenyl)-2-(4-sulphophenyl)-2H-tetrazolium (MTS) assay, 4′-6-diamidino-2-phenylindole (DAPI) staining and western blot analysis. HESO was found to inhibit cell growth and induce apoptosis in HSC4 and HN22 oral cancer cells. HESO downregulated myeloid cell leukemia-1 (Mcl-1) in HSC4 cells and was associated with the activation of Bak, resulting in Bak oligomerization on the mitochondrial outer membrane. HESO did not alter Mcl-1 expression in HN22 cells, but it decreased Sp1 expression. The downregulation of Sp1 by HESO in HN22 cells resulted in a decrease in survivin, a downstream target protein of Sp1. These results suggested that HESO inhibited the growth of oral cancer through either Mcl-1 or Sp1, indicating that HESO may serve as a potential drug candidate against oral cancer.